Effects of Bariatric Surgeries on Fetuin-A, Selenoprotein P, Angiopoietin-Like Protein 6, and Fibroblast Growth Factor 21 Concentration - Jakub Poloczek; Wojciech Kazura; Ewa Kwaśnicka; Janusz Gumprecht; Jerzy Jochem; Dominika Stygar (Journal of Diabetes Research)
Obesity is a civilization disease representing a global health problem. Excessive body weight significantly reduces the quality of life. It is also associated with the leading causes of death, including type 2 diabetes mellitus, cardiovascular diseases, and numerous types of cancer. The mainstay of therapy is a dietary treatment. However, in morbidly obese patients, dietary treatment is often insufficient. In these patients, the most effective procedure is bariatric surgery, but it is still difficult to predict its outcome and metabolic changes. Hepatokines are proteins secreted by hepatocytes. Many of them, including fetuin-A, selenoprotein P, angiopoietin-like protein 6, and fibroblast growth factor 21, have been linked to metabolic dysfunctions. In this context, hepatokines may prove helpful. This review investigates the possible changes in hepatokine profiles after selected bariatric surgery protocols. In this regard, Roux-en-Y gastric bypass is the most studied type of surgery. The overall analysis of published research identified fetuin-A as a potential marker of metabolic alternations in patients after bariatric surgery.